Inhibition of G Protein-Activated Inwardly Rectifying K(+) Channels by Phencyclidine - Kobayashi, Toru (Bentham Science Publishers Ltd, 2011)
Addictive drugs, such as opioids, ethanol, cocaine, amphetamine, and phencyclidine (PCP), affect many functions of the nervous system and peripheral organs, resulting in severe health problems. G protein-activated inwardly rectifying K(+) (GIRK, Kir3) channels play an important role in regulating neuronal excitability through activation of various Gi/o protein-coupled receptors including opioid and CB(1) cannabinoid receptors. Furthermore, the channels are directly activated by ethanol and inhibited by cocaine at toxic levels, but not affected by methylphenidate, methamphetamine, and 3,4-methylenedioxymethamphetamine (MDMA) at toxic levels. The primary pharmacological action of PCP is blockade of N-methyl-D-aspartate (NMDA) receptor channels that are associated with its psychotomimetic effects. PCP also interacts with several receptors and channels at relatively high concentrations. However, the molecular mechanisms underlying the various effects of PCP remain to be clarified. Here, we investigated the effects of PCP on GIRK channels using the Xenopus oocyte expression system. PCP weakly but significantly inhibited GIRK channels at micromolar concentrations, but not Kir1.1 and Kir2.1 channels. The PCP concentrations effective in inhibiting GIRK channels overlap clinically relevant brain concentrations in severe intoxication. The results suggest that partial inhibition of GIRK channels by PCP may contribute to some of the toxic effects after overdose.